1991
DOI: 10.1080/00221689109498991
|View full text |Cite
|
Sign up to set email alerts
|

Drag on vertical sill of forced jump

Abstract: As a basis for designing a forced-hydraulic-jump-type stilling basin, the pressure magnitude on the upstream and downstream faces of a continuous-vertical sill has been investigated experimentally, and the nature of the pressure distribution on the faces of the sill has been discussed. Furthermore, an experimental formula for the drag force acting on the sill has been proposed considering the characteristics of the flow condition over the sill. RESUME L'étude experimental des pressions aux parois a été réalisé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…McCorquodale & Mohamed (1994) proposed a theoretical approach based on conservation of momentum principles to estimate hydraulic jump characteristics and found that the stability of a hydraulic jump on an adverse slope is also dependent on the upstream Froude number. The presence of a sill increases hydraulic jump stability for both horizontal (Hager & Bretz, 1988;Othsu, 1981;Ohtsu, Yasuda, & Yamanaka, 1991) and adverse-sloped beds (Pagliara & Peruginelli, 2000). In particular, Pagliara & Peruginelli (2000) conducted a series of experimental tests with and without a sill, varying the bed slope from 0 to -20% (adverse slope).…”
Section: Introductionmentioning
confidence: 97%
“…McCorquodale & Mohamed (1994) proposed a theoretical approach based on conservation of momentum principles to estimate hydraulic jump characteristics and found that the stability of a hydraulic jump on an adverse slope is also dependent on the upstream Froude number. The presence of a sill increases hydraulic jump stability for both horizontal (Hager & Bretz, 1988;Othsu, 1981;Ohtsu, Yasuda, & Yamanaka, 1991) and adverse-sloped beds (Pagliara & Peruginelli, 2000). In particular, Pagliara & Peruginelli (2000) conducted a series of experimental tests with and without a sill, varying the bed slope from 0 to -20% (adverse slope).…”
Section: Introductionmentioning
confidence: 97%
“…where is the distance between the hydraulic jump toe and the upstream face of the sill and the hydraulic jump length is obtained as = 5.5 2 * . The drag coefficient obtained for the presented models using the definition by Ohtsu et al [76] was in the line of their experimental results.…”
Section: Pressures Analysissupporting
confidence: 84%
“…In particular, the research by Rahmeyer discussed several alternate designs to replace the full height sidewalls of the basin. Ohtsu et al [76] conducted an experimental study to determine the drag force on stilling basin sills. On the basis of their observations, these authors proposed an expression to obtain the drag coefficient, which was used to contrast the results of this research (section 5.5).…”
Section: Stilling Basins Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in the past studies, the effect of sill height on energy dissipation ratio, turbulence intensity, the length of hydraulic jump and roller was not examined in the case of the same Froude number. In addition, while the hydraulic jump occurring after the sluice gate was examined in the previous studies, in this study the hydraulic jump is evaluated in the stilling basin after the spillway chute channel ( [33,34,12,35,36,21,37]. For these reasons, this study has differences from the existing literature, and it is thought to contribute to the literature.…”
Section: Introductionmentioning
confidence: 99%